Ethylene-induced leaf senescence depends on age-related changes and OLD genes in Arabidopsis - Jing, Hai-Chun (Journal of experimental botany, 2005)
Ethylene can only induce senescence in leaves that have reached a defined age. Thus, ethylene-induced senescence depends on age-related changes (ARCs) of individual leaves. The relationship between ethylene and age in the induction of leaf senescence was tested in Arabidopsis Ler-0, Col-0, and Ws-0 accessions as well as in eight old (onset of leaf death) mutants, isolated from the Ler-0 background. Plants with a constant final age of 24 d were exposed to ethylene for 3-16 d. The wild-type accessions showed a common response to the ethylene treatment. Increasing ethylene treatments of 3-12 d caused an increase in the number of yellow leaves. However, an ethylene exposure time of 16 d resulted in a decrease in the amount of yellowing. Thus, ethylene can both positively and negatively influence ARCs and the subsequent induction of leaf senescence, depending on the length of the treatment. The old mutants showed altered responses to the ethylene treatments. old1 and old11 were hypersensitive to ethylene in the triple response assay and a 12-d ethylene exposure resulted in a decrease in the amount of yellow leaves. The other six mutants did not show a decrease in yellow leaves with an ethylene treatment of 16 d. The results revealed that the effect of ethylene on the induction of senescence can be modified by at least eight genes